1020 UTILITY OF CARDIAC MAGNETIC RESONANCE FOR INITIAL AND FOLLOW-UP EVALUATION OF A PATIENT WITH COMPLICATED ACUTE MYOCARDITIS. (15th December 2022) - Mariani, Andrea; Scatteia, Alessandra; Frecentese, Francesca; Pascale, Carmine Emanuele; Russo, Giuseppe; Esposito, Giovanni; Dellegrottaglie, Santo
Abstract: A 20-year-old woman with a history of pneumonia, polycystic ovarian syndrome and ovarian teratoma asportation presented with chest pain and worsening dyspnoea. No prodromal or concomitant infective symptoms were reported. On admission, vital parameters were within normal limits, ECG was unremarkable and laboratory tests revealed high white blood cells count and increased hs-cTnI. Transthoracic echocardiography showed diffuse left ventricular (LV) dysfunction, with akinesia of basal segments and a severely reduced ejection fraction (LVEF = 27%). A full heart failure drug treatment was gradually introduced and, after two weeks, a cardiac magnetic resonance (CMR) was performed. CMR showed significant but incomplete recovery of LV systolic function (LVEF = 40%), extensive areas of myocardial oedema with diffuse LV involvement on STIR (short tau inversion recovery) images (Fig. A ) and, almost with the same LV distribution, considerable late gadolinium enhancement (LGE) with subepicardial/intramyocardial distribution on post-Gadolinium images (Fig. B-C); all these findings strongly suggested an acute myocarditis with diffuse LV myocardial damage. Definitive diagnosis was made through endo-myocardial biopsy, that revealed significant infiltration of lymphocytes, without additional specific elements. Patient was sent home with an optimized drug therapy for heart failure with reduced ejection fraction and a close clinical follow-up was prescribed. Roughly a month after discharge the patient presented with sustained ventricular tachycardia that required prompt admission and DC shock. Hence, an MR-conditional transvenous ICD was implanted without complications. After 7 months from the acute event, patient underwent a follow-up CMR that, despite artifacts produced by ICD generator and intracavitary leads, still displayed reduced LV systolic function (LVEF = 41%) and extensive LGE with a non-ischemic "ring-like" LV pattern (Fig. D-E) . Finally, patient has been put on the waiting list for heart transplantation and, in order to exclude left-dominant arrhythmogenic cardiomyopathy (LDAC), genetic tests have been ordered, but are still pending. The present case emphasizes the importance of CMR for the initial assessment of patients with acute myocarditis: beyond the crucial role in evaluating extension and severity of the inflammatory process at the myocardial level, it can identify specific features (i.e. ring-like or antero-septal patterns of LGE involvement), more frequently reported in high-risk subgroups, such as LDAC, with suggestion for further investigations (including genetic tests for desmosomal mutations). During follow-up, CMR retains a central role to evaluate possible changes in ventricular function and in extension of myocardial tissue involvement, useful to guide the cardiologist to choose for a more tailored management and define a more precise timing for further follow-up. Progressive expansion of CMR indications is helping to understand the pathophysiology of many cardiac conditions (including myocarditis and myocarditis-like entities) and many of the previous limitations to its wider clinical use have progressively been settled. From the present case, it can be appreciated how, even in presence of an implanted cardiac device, precious diagnostic information can still be obtained using CMR. However, to ensure safety and feasibility, MR-conditional devices need to be appropriately checked and reprogrammed before and immediately after the exam, while adapted CMR imaging protocols and adequate patient monitoring need to be applied during the scan.